Pembuatan Produk Fermentasi Yogurt Sebagai Pangan Sehat Bagi Guru MTs Arifah Gowa - Muhtar, Rachmawaty; Suryani, A. Irma; Yusuf, Yusnaeni (Universitas Sulawesi Barat, 2023)
The training activity for making fermented yogurt products, conducted at MTS Arifah Gowa, aims to empower MTS teachers and enhance the knowledge of training participants regarding the production of fermented yogurt products as a healthy, convenient, and cost-effective food item with economic value. This activity was conducted in three stages: firstly, providing materials and facilitating discussions with participants; secondly, instructing them in the proper and correct yogurt-making practices; and finally, conducting an evaluation and administering a questionnaire to assess the participants' responses to the training activities provided. Based on the results of the questionnaire evaluation, all training participants expressed satisfaction with this activity, achieving a score of (3.64), indicating that the evaluation results fall within the